Using regression tree analysis to determine size class intervals and sexual dimorphism in the Morelet's crocodile Crocodylus moreletii. Issue 4 (8th October 2020) - Padilla, Sergio E.; González‐Jáuregui, Mauricio; Von Osten, Jaime Rendón; Valdespino, Carolina; López Luna, Marco A.; Quiróz, Gabriel Barrios; Barão‐Nóbrega, José António L.
Abstract : Assignment of Morelet's crocodile Crocodylus moreletii individuals into size groups or classes based on ecological and morphological similarities has not yet been associated with species‐specific ontogeny related changes. Age or size of first reproductive behavior is not precisely known for C. moreletii, but differences in allometric patterns and relative cranial size between juveniles and adults might be used as an indicator of sexual maturity. In this study, a regression tree analysis was used to investigate the relationship between age and body size in 1266 crocodiles by using both simple and generalized linear models, with gender and origin (captivity or wild) as factors. Total length (TL), snout–vent length (SVL) and cranial length (CL) were used as predictor variables and the logarithm of body mass as the response variable. Four length intervals with well‐defined thresholds (514, 899 and 1497 mm of TL) were established using all three predictors (TL, SVL and CL). Relationship between SVL and TL was described, and a strong positive relationship (r 2 = 0.98), unaffected by crocodile gender, was observed. The observed CL–TL and CL–SVL relationships were also positive but significantly different between males and females (p < 0.001) and length interval classes (p = 0.01). These results suggest that our estimated size thresholds seem to correspond to important ontogenetic changes in C. moreletii and that sexual maturity is closely related to size in this species, where sexual dimorphism in body length occurs, particularly in large individuals (size group IV).